Students’ perception of social presence in the online EFL speaking class - Kusumaningtyas, Brigita Woro Diyatni; Mukti, Thomas Wahyu Prabowo (Universitas Islam Negeri Banda Aceh, 2023)
Some students claim to suffer from anxiety, which lowers their self-esteem and causes them to feel anxious and uneasy while studying a foreign language. Establishing a social connection between the lecturer and the students is one of the possible solutions to this issue. The purpose of this study was to examine students' perceptions of social presence in an online speaking class and how social presence affects students' confidence in speaking class. This study employed quantitative research as its method of inquiry. The researchers distributed questionnaires to 159 students to collect data, but only 51 students responded. In addition, the researchers conducted interviews with a subset of participants to gain additional insight into the data required for the study. The research findings on students' perception of social presence in the online speaking class and the effect of social presence on students' confidence in speaking class revealed that students had a favorable perception of social presence in the online speaking class. The first finding's mean score was seventy-two point nine (x ̅ = 72.9). The findings demonstrated that social presence influences students' self-confidence, encourages them to learn more, and assists students in improving their speaking ability in speaking class.